PENERAPAN AKUNTANSI LINGKUNGAN (Studi Kasus Pada PT Semen Indonesia (Persero) Tbk Tuban) - Ismie Dzakky Fatimah (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analyze the application of environmental accounting realized as CSR program of PT Semen Indonesia (Persero) Tbk Tuban using Triple Bottom Line perspectives. The type of research is a qualitative descriptive study. The data are obtained from the company’s documents which are relevant to CSR program as well as interviews with several employees and the communities around the company. The model of Miles, Huberman and Saldana is used as a data analysis method using an interactive data analysis model. The Results of research show that in overall PT Semen Indonesia has implemented the perspective of Triple Bottom Line in its CSR program. The company has conducted social programs for communities around the company, the education, infrastructure, as well as environmental sustainability-based community development programs and improve living standard around the company. Lack of supports and coordination with government of Tuban and societies have been found to be the constraints of CSR program implementation. Moreover, CSR programs tend to be directed as charity programs which hence the programs do not have fully reciprocal relationship with communities.Keywords: CSR, environmental accounting, Triple Bottom Line